DNM1L-Related Mitochondrial Fission Defects Presenting as Encephalopathy: A Case Report and Literature Review - Liu, Xingmiao; Zhang, Zhongbin; Li, Dong; Lei, Meifang; Li, Qing; Liu, Xiaojun; Zhang, Peiyuan (Frontiers in Pediatrics, 2021)
Background: Mitochondrial dynamics, including mitochondrial fission and fusion, transport and distribution, biogenesis and degradation, are critical to neuronal function. The dynamin-1 like (DNM1L) gene encodes dynamin-related protein 1 (DRP1/DLP1), which is an evolutionarily conserved member of the dynamin family and is responsible for mitochondrial division. DNM1L variants can lead to mitochondrial fission dysfunction and neurological disorders. Methods: We report a case of DNM1L-related mitochondrial disease admitted to Tianjin Children's Hospital. We searched for similar reported cases in the PubMed database using the terms “DNM1L” and “mitochondrial”, reviewed recent literature to summarize the clinical and genetic characteristics, and analyzed genotype-phenotype correlations. Results: The patient presented with psychomotor retardation, motor disturbance (muscle weakness with paroxysmal hypermyotonia), and a de novo variant (c.116G>A, g.22229G>A, p.S39N) in the GTPase domain of DNM1L (reference sequence NM_012062), which has not previously been reported in the literature. This case was combined with an additional 35 cases identified in 20 relevant references in order to analyze a total of 36 patients. The male-to-female ratio was 1:1.06, and the median age of onset was 6 months (range, neonatal period to 9 years). The cardinal symptoms included psychomotor retardation in 77.8% (28/36), limb paralysis in 66.7% (18/27), dystonia in 82.8% (24/29), and epilepsy in 59.4% (19/32). The clinical manifestations of variants in the GTPase domain of DRP1 were milder than those identified in the middle domain. Conclusion: This case report describes a new variant of the DNM1L gene, and summarizes previously reported cases. Furthermore, the clinical phenotype and the genotype of DNM1L gene-associated mitochondrial disease was analyzed to improve the understanding of this disease.